Performance evaluation of an evaporative charcoal cooler and its effects on quality of leafy vegetables - Ronoh, Erick K; Kanali, Christopher L; Ndirangu, Samuel N; Mang oka, Samson M; John , Annpurity W (Journal of Postharvest Technology, 2018)
Preservation is a critical process used for handling fresh produce such as vegetables while maintaining their quality. This study focused on an evaporative cooling system for use by smallholder farmers. The technique was adopted for preservation of leafy vegetables based on its availability and affordability. The study aimed at evaluating the technical performance of an evaporative charcoal cooler and its effects on the quality of amaranth and spinach. The cooler microclimate and ambient conditions were investigated by measuring air temperature and relative humidity. The maximum cooling potential for the cooler was found to be 16.85°C while the maximum relative humidity difference between the cooler and outdoor conditions was found to be 38.07%. The charcoal cooler attained the highest relative humidity and the lowest temperatures. The analysis indicated that vitamin C, colour and weight of spinach and amaranth reduced with storage time. Based on a usable limit of 70% loss in moisture content, the shelf-life of amaranth was increased from two days in the control environment (outdoors) to seven days in the cooler, while that of spinach increased from three days to nine days. Overall, the charcoal cooler is beneficial in extending the shelf-life of leafy vegetables and preserving their quality.